Association of Barrett's esophagus with infection: a meta-analysis - Shaoze Ma; Xiaozhong Guo; Chunmei Wang; Yue Yin; Guangqin Xu; Hongxin Chen; Xingshun Qi (SAGE Publishing, 2022)
Background and Aims: Barrett's esophagus (BE) is the only recognized precursor for esophageal adenocarcinoma. Helicobacter pylori ( H. pylori ) infection is a major contributing factor towards upper gastrointestinal diseases, but its relationship with BE remains controversial. Some previous studies suggested that H. pylori infection negatively correlated with BE, while others did not. This may be attributed to the difference in the selection of control groups among studies. The present meta-analysis aims to clarify their association by combining all available data from well-designed studies. Methods: The PubMed , EMBASE , and Cochrane Library databases were searched. Odds ratios (ORs) with 95% confidence intervals (CIs) were pooled by a random-effects model. Heterogeneity was evaluated using the Cochran's Q test and I 2 statistics. Meta-regression, subgroup, and leave-one-out sensitivity analyses were employed to explore the sources of heterogeneity. Results: Twenty-four studies with 1,354,369 participants were included. Meta-analysis found that patients with BE had a significantly lower prevalence of H. pylori infection than those without (OR = 0.53, 95% CI = 0.45-0.64; p  < 0.001). The heterogeneity was statistically significant ( I ² = 79%; p  < 0.001). Meta-regression, subgroup, and leave-one-out sensitivity analyses did not find any source of heterogeneity. Meta-analysis of 7 studies demonstrated that CagA-positive H. pylori infection inversely correlated with BE (OR = 0.25, 95% CI = 0.15-0.44; p  = 0.000), but not CagA-negative H. pylori infection (OR = 1.22, 95% CI = 0.90-1.67; p  = 0.206). Meta-analysis of 4 studies also demonstrated that H. pylori infection inversely correlated with LSBE (OR = 0.39, 95% CI = 0.18-0.86; p  = 0.019), but not SSBE (OR = 0.73, 95% CI = 0.30-1.77; p  = 0.484). Conclusion: H. pylori infection negatively correlates with BE. More experimental studies should be necessary to elucidate the potential mechanisms in future.